Simulation and optimization of silicon solar cell using MgF₂/SiO₂ double - Layer Anti - Reflective Coating (ARC) / Nur Fatin Najwa Razali - Razali, Nur Fatin Najwa; Mohmad Salleh, Siti Hajar; Mohd Yusoff, Mohd Zaki (Universiti Teknologi MARA Shah Alam, 2022)
The most common method of harnessing solar energy is photovoltaic. With the revolution of new energy innovation in recent years, generation of electricity based on photovoltaic has possessed great progress, however, high cost is one of the primary issues encountered. In order to drive into a better manufacturing technology, the effectiveness of the cells and modules is opt for further cost reduction. The purpose of this research is to study the parameter on crystalline silicon solar cell with double layer of MgF₂/SiO₂ as its anti-reflective coating (ARC) which is the thickness. An antireflection coating mostly introduced in solar cell in order to reduce the reflection of light from the front surface of the cell and to enhance broadband of light absorption. Four Light trapping (LT) scheme with double layer of MgF₂/SiO₂ and adjusted thickness on 100 µm thin crystalline silicon(c-Si) was investigated. The optical properties within 300-1200 nm wavelength region were analyzed and from absorption curve, maximum potential photocurrent density (Jmax) for each LT schemes was calculated. With the addition of ARC into the c-Si, the Jmax increased up to 32.13 mA/cm2 and achieved 28.89 % enhancement compared to the Jmax of the c-Si reference (without ARC). Therefore, it is important to achieve optimum value in absorption that literally showed the excellent optical property of MgF₂/SiO₂ bilayer coatings.